He has opened Nisaba's house of learning : studies in honor of Åke Waldemar Sjöberg on the occasion of his 89th birthday on August 1st 2013 - Sjöberg, Åke W.; Sassmannshausen, Leonhard.; Neumann, Georg. (Cuneiform Monographs, 2014)
In He has Opened Nisaba's House of Learning twenty-six scholars honor Åke Sjöberg, professor emeritus of Assyriology at the University of Pennsylvania and former editor of the Pennsylvania Sumerian Dictionary . The twenty-one studies included focus on Mesopotamian wisdom literature, religious texts, cultural concepts, the history of writing, material culture, society, and law from the invention of writing to the Hellenistic period. The volume includes editions of several previously unpublished texts.